HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN RESILIENSI PADA PARA SUSTER YUNIOR DI KOTA YOGYAKARTA - Lusia Lenisia Tima; Titik Muti'ah (JURNAL SPIRITS, 2014)
ABSTRACTThis study is a correlation research that is intended to determine whether there is a correlation between emotional intelligence and resilience of the junior nuns. The method used is the Pearson Product-moment method of correlation studies. The sample was 85 nuns who live in the city of Yogyakarta. This study used two scales as a measurement tool, namely the scale of emotional intelligence and resilience were prepared by the researcher in the form of Likert Scale. Number of all items is 55 items consisted of 38 items from resilience and 17 items emotional intelligence. The scale emotional intelligence has a reliability of 0.790 resilience andscale of resilience has reliability of 0.899.The results were analyzed using SPSS for windows version 16 release. The results indicate a positive and significant relationship between emotional intelligence and resilience, with a coefficients correlation of 0.870 and significance level, 0.00 (p<0.05). With this it can be said that the hypothesis that there is a positive relationship between emotional intelligence and resilience acceptable. Effective contribution to the study of 75.7%, amounting to 75.7% meaning that resilience is determined by emotional intelligence. Higher emotional intelligence also increasingly steeper resilience.Â Keyword: Recilience,emotional intelligence, the Junior Nuns